Kejadian Stunting pada Anak Usia Balita - Nurjanna Adil Wael; Sunarti; Fatma Jama; Nur Ilah Padhila (Window of Nursing Journal, 2025)
Stunting (short) according to WHO in 2020 is a growth disorder in children caused by chronic malnutrition or chronic infectious diseases as indicated by the z-score value of height for age. This study aims to determine the factors associated with the incidence of stunting in children under five at the Kassi-Kassi Makassar Health Center. This research is a quantitative study using a cross-sectional approach in the nursing program at the Indonesian Muslim University. The population of this study was 154 people and the sample was taken using the total sampling method. The tests in this study were chi square analysis with the level of food (ρ > 0.05). The results of the study showed that there was a relationship between a history of exclusive breastfeeding and the incidence of stunting in children under five at the Kassi-Kassi Makassar Health Center, as shown by the results of statistical tests. There is a relationship between the history of low birth weight LBW babies and the incidence of stunting in children under five at the Kassi-Kassi Makassar Health Center. There is a relationship between the provision of complementary feeding to the incidence of stunting in children under five at the Kassi-Kassi Makassar Health Center as shown by the results of statistical tests.